effectiveness Effectiveness of Health Education in Improving Adolescents' Knowledge and Attitudes Towards the Risk of Diabetes Mellitus - Diah Ayu Putri Tunggal Dewi; Dimas Ria Angga Pribadi (Indonesian Journal of Global Health Research, 2026)
Diabetes mellitus is one of the global health problems with an increasing prevalence, including among young age groups. Frequent consumption of sugary drinks can increase the risk of type 2 diabetes, so adolescents need health education to improve their knowledge and attitudes about the dangers of excessive sugar intake. This research aims to determine the effectiveness of health education in increasing adolescents' awareness about the dangers of consuming jumbo iced tea on the risk of diabetes mellitus. This study used a quantitative quasi-experimental design with 92 respondents selected through convenience sampling. The intervention consisted of health education through presentations, leaflets, and online mentoring for one week. Data were collected using a knowledge and attitude questionnaire and analyzed using the Paired and Independent Sample T-Test with a significance of α = 0.05. The research results show that health education significantly increased adolescents' knowledge and attitudes toward the dangers of consuming jumbo iced tea and the risk of diabetes (p-value = 0.001 for knowledge; p = 0.001 for attitudes). This research demonstrates that health education delivered through classroom presentations, educational leaflets, and monitoring via groups for one week is effective in improving adolescents' knowledge and attitudes. Therefore, this method can be adopted as an effective health promotion strategy in the future.